Retinol and Alpha-tocopherol in the Colostrum of Lactating Tunisian Women Delivering Prematurely: Associations with Maternal Characteristics - Samira Fares; Mohamed Marouane Sethom; Samia Kacem; Imen Ksibi; Moncef Feki; Sami Jebnoun; Naziha Kaabachi (Elsevier, 2016)
This study aims to assess vitamin A and E concentrations in the premature colostrum of lactating Tunisian women and to identify maternal characteristics that may affect these concentrations. Methods: Human colostrum was obtained from 105 mothers who gave birth prematurely in the Centre for Maternity and Neonatology of Tunis (Tunisia). Retinol and alpha-tocopherol were analyzed in the colostrum and in plasma by high-performance liquid chromatography. Results: Retinol and alpha-tocopherol concentrations were 57.5 ± 50.1 μg/dL and 1222 ± 772 μg/dL in the colostrum, respectively, and 51.7 ± 20.0 μg/dL and 1351 ± 772 μg/dL in plasma, respectively. Concentrations of each vitamin in the colostrum were positively correlated with their respective concentrations in plasma (r = 0.415, p = 0.001 for retinol and r = 0.392, p = 0.003 for alpha-tocopherol). In multivariate analysis, colostrum vitamin A was associated with plasma vitamin A and preeclampsia, while colostrum vitamin E was associated with plasma vitamin E, gestational age, and preeclampsia. Conclusion: In Tunisian women, colostrum vitamin A and E levels are close to the average values reported in the literature. The levels are too low to cover the needs of very low birth weight (VLBW) infants, particularly in women with plasma vitamin deficiencies, preeclampsia, or very premature delivery. Given the undeniable beneficial effects of human colostrum, whenever feasible, VLBW infants should be fed colostrum. Infant vitamin A and E requirements should be met by milk fortification or supplementation.